IMPLEMENTASI KURIKULUM DARURAT MASA COVID-19 DI MIN LIMA PULUH KOTA - Susi Hariyati; Misfa Misfa; Muhammad Agus Suryana; Iswantir Iswantir (JURNAL MANAJEMEN PENDIDIKAN, 2022)
Emergency Curriculum is an education unit level curriculum that is prepared and implemented by education units during an emergency by taking into account the applicable regulatory signs and the limited conditions of each educational unit during an emergency. The purpose of the study was to determine the level of implementation of the emergency curriculum at state madrasah, and to determine the process of implementing learning during the Covid-19 pandemic. This research is quantitative research. Data collection techniques using questionnaires. The objects of this research are teachers at the State Islamic School (MIN) Lima Puluh Kota. The results of the research on aspects of the implementation of the emergency curriculum, the application of learning principles, the implementation of learning activities, and the evaluation of learning showed a high category. This means that the emergency curriculum has been socialized and implemented in madrasah. as well as teachers who have implemented aspects of the curriculum in the learning process. The geographical conditions and situations where students live must be a concern in implementing distance learning using internet media, because in certain conditions the network is not capable of being used so that the learning process does not take place optimally. In the learning process, teachers still have to consider the conditions, needs and characteristics of each student (related to student conditions), accommodate different student conditions, support facilities, learning styles and learning needs. There are some students who are constrained by the network, learning tools, and the use of learning media.